Diagnosis dan Tatalaksana Postherpetic Neuralgia - Ali Ramzi; Firza, Fatimah (Faculty of Medicine, Universitas Mataram, 2025)
Postherpetic Neuralgia (PHN) is a chronic pain condition that occurs after the resolution of Herpes zoster, significantly affecting patients’ quality of life. PHN is characterized by spontaneous pain, hyperalgesia, allodynia, and paresthesia. Major risk factors include advanced age, severity of rash, and ophthalmic involvement. The pathophysiology involves reactivation of the varicella-zoster virus (VZV), leading to nerve inflammation and peripheral sensitization. Management of PHN includes analgesics, antiepileptic drugs (pregabalin, gabapentin), antidepressants, and topical therapies such as capsaicin and lidocaine. Prevention can be achieved through zoster vaccination. Combination therapy is often required to optimize treatment outcomes in PHN.